Managing a Tenancy: Young people's pathways into and sustaining independent tenancies from homelessness - Stewart, Alasdair B. R. (2013)
Due to their disproportionate risk of tenancy non-sustainment there have been concerns raised for young people making a pathway out of homelessness into independent living. Despite these concerns, there has been limited research looking at how young people experience tenancy sustainment or where they move onto after terminating a tenancy. This thesis, drawing on Bourdieu’s (1990a) theory of practice, presents a reconceptualisation of tenancy sustainment as a practice of sustaining a tenancy. The theoretical-empirical analysis is based on data collected through longitudinal research involving two waves of semi- structured interviews with 25 young people, aged 16-25, who had recently made a pathway out of homelessness into their own independent tenancies. The interdependency between a tenant and their tenancy presented young people with pressures which they developed techniques of independent living in response to in order to sustain their tenancy and make it a home. Young people not only had a particular housing position of being a tenant, they held family and education-employment positions which took part in the formation and shaping of the pressures they experienced living independently. Tenancies were not seen as an end in themselves by young people who desired, through the experience of sustaining a tenancy, increasingly independent positions within their other social positions as well. An uneven process of actually existing neoliberalism across policy areas through its influence on young people’s constellation of interdependent relations also created a dissonance within the positions held by young people fostering social suffering. Young people ending a tenancy viewed this as a ‘step backwards’ when it meant decreasing independence such as a return to supported accommodation; ambivalence where it arose from the end of a relationship; and as a move forwards, or ‘getting on with life’, when making a youth transition and housing pathway towards establishing their own family household